Analisis Pelatihan dan Kepuasan Kerja terhadap Kinerja Karyawan yang Dimoderasi oleh Masa Kerja - Nika, Pingka Berlia; Anatan, Lina (Jurnal Informatika Ekonomi Bisnis, 2025)
In the era of digital transformation, improving employee performance has become a major challenge for companies to remain competitive. This study aims to analyze the effect of training and job satisfaction on employee performance, with tenure as a moderating variable, at PT RK Branch Cibeureum, Bandung City. Using a quantitative approach, data were collected through questionnaires distributed to 64 respondents employees selected using a simple random sampling method. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the SmartPLS 4 software. The results show that both training and job satisfaction have a positive and significant effect on employee performance, with job satisfaction emerging as the most dominant factor. However, tenure does not have a significant influence, either directly or as a moderating variable. These findings emphasize that employee performance improvement depends more on the effectiveness of training programs and the level of job satisfaction rather than the length of service. Therefore, companies should prioritize the development of relevant training programs and implement strategies to enhance job satisfaction in order to optimize employee performance.